Traditional medicines used by Q'eqchi' Maya to treat diabetic symptoms and their antiglycation potential. (5th October 2018) - Ferrier, J.; Saleem, A.; Carter Ramirez, A.; Liu, R.; Chen, E.; Pesek, T.; Cal, V.; Balick, M.; Arnason, J.T.
Abstract: Ethnopharmacological relevance: Because of the recent increase in type 2 diabetes and the need for complementary treatments in remote communities in many parts of the world, we undertook a study of treatments for diabetic symptoms used by traditional Q'eqchi' Maya healers of Belize. We used quantitative ethnobotany to rank culturally important taxa and subsequent pharmacological and phytochemical studies to assess bioactivity. Materials and methods: Antidiabetic plants identified in field interviews with traditional healers were ranked by syndromic importance value (SIV) based on 15 symptoms of diabetes. Species ranked with high SIV were tested in an assay relevant to many diabetes complications, the advanced glycation endproduct (AGE) inhibition assay. Active principles were identified by phytochemical analysis and bioassay. Results: We collected over 70 plant species having a promising SIV score. The plants represented a broad range of neotropical taxa. Selected Q'eqchi' antidiabetic plants with high SIV were collected in bulk and tested in the advanced glycation endproduct (AGE) inhibition assay. All plant extracts showed AGE inhibition and the half maximal inhibitory concentration (IC50 ) ranged from 40.8 to 733 µg/mL, while the most active species was Tynanthus guatemalensis Donn (Bignoniaceae). A linear regression showed a significant relationship between 1/ IC50 and SIV. Phytochemical analysis revealed the presence of verbascoside, as a major component and active principle of the T guatemalensis which had an IC50 = 5.1 µg/mL, comparable to the positive control quercetin. Conclusion: The results reveal a rich botanical tradition of antidiabetic symptom treatments among the Q'eqchi'. Study of highly ranked plants revealed their activity in AGE inhibition correlated with SIV. T. guatemalensis was identified as a promising species for further evaluation and local use. Graphical abstract: fx1